PREDICTING YOUNGSTER’S ATTITUDE TOWARDS ONLINE FOOD DELIVERY - Dave, Anupama Chirag; Trivedi, Rinky (Universitas Prasetiya Mulya, 2019)
Attitude has been a very significant topic in the area of consumer research owing to the role it plays in the consumer decision making process. Literatures have identified various models that can measure attitude; for this research ABC model of attitude was used. The purpose of this study was to measure the attitude of respondents for OFD and their by analyzing the impact of each component of ABC model on Attitude creation. The data was collected from 368 youngsters using a structured questionnaire. Using SPSS 21, computer software the type of attitude was measured and for achieving second objective AMOS 21.0 software was used. Once the model fit was achieved using AMOS 21.0 the structured equation modeling was performed. The investigation revealed that youngsters have moderately positive attitude towards Online Food Delivery (OFD) and it was the affective component of attitude that had the highest influence on attitude creation.